IMPLEMENTASI UTA DAN MAUT PADA SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN SOSIAL DI DESA WONGA WEA - Veronika Agustina Meo; Meliana O. Meo (Jurnal Publikasi Manajemen Informatika, 2026)
The provision of social assistance in Wonga Wea Village still experiences several problems, including the provision of assistance often experiencing inaccuracy in selecting residents who receive social assistance, because currently many wealthy residents receive social assistance which assistance should be given to the less fortunate. To overcome this problem, a decision support system for receiving social assistance was created using the application of the UTA (Utility Theory Additive) and MAUT (Multi Attribute Utility Theory) methods. UTA is used to assess the utility of each prospective recipient based on predetermined criteria while MAUT helps in integrating various criteria with appropriate weights so that the decision-making process becomes more systematic and structured. Therefore, the process of receiving social assistance using the application of the UTA (Utility Theory Additive) and MAUT (Multi Attribute Utility Theory) methods can help village officials in Wonga Wea Village in the process of data collection and decision-making to determine eligible recipients of social assistance so that there are no errors in the process of receiving social assistance. This study tests the hypothesis that the application of the UTA (Utility Theory Additive) and MAUT (Multi Attribute Utility Theory) methods can improve the accuracy of the selection of social assistance recipients, so that assistance is more targeted to people who really need it. The results of the study indicate that the system created is able to improve the accuracy of the selection of assistance recipients compared to conventional methods.